TINGKAT KECEMASAN IBU HAMIL SELAMA MASA PANDEMI COVID-19 DI KOTA DENPASAR, BALI, INDONESIA - Harini, I Gusti Ayu Agung Diah; Aryani, Putu; Cintya Denny Yuliyatni, Putu; Citra Wulan Sucipta Putri, Wayan (E-Jurnal Medika Udayana, 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, changes in income, employment, and social interactions have affected the psychological condition of all groups of people, including pregnant women. In pregnant women, anxiety during the pandemic is related to the threat of COVID-19 to the lives of mothers and babies as well as concerns about unmet prenatal care needs, relationship tensions, and social isolation during the COVID-19 pandemic. Unfortunately, data on the prevalence of anxiety levels of pregnant women during the COVID-19 pandemic are still quite limited. The purpose of this study is to find out the level of anxiety of pregnant women during the COVID-19 pandemic, especially in Denpasar City, Bali, Indonesia. This research is a descriptive research with cross sectional approach conducted on 140 pregnant women who examined their pregnancy at several health centers in Denpasar during February - November 2020 by using a google form containing questions about maternal characteristics and hamilton rating scale for anxiety (HRS-A) questionnaire to measure maternal anxiety levels. The data is analyzed using SPSS 22 program and presented in the form of frequency and percentage tables and graphs. The results showed that 55% of mothers did not experience anxiety, 28.6% of mothers experienced mild anxiety, 12.9% of mothers experienced moderate anxiety and 3.6% of mothers experienced severe anxiety. In general, anxiety in pregnant women can be influenced by the pregnant mother’s characteristics such as age, recent education, occupation, income, pregnancy trimester and maternal gravida status whose prevalence will be further explained in this study. The results of this study present data on the prevalence of anxiety levels in pregnant women during the COVID-19 pandemic that may have differences with the prevalence of anxiety of pregnant women before the COVID-19 pandemic. Keywords : Anxiety, Pregnancy, Pandemic, COVID-19